Translation Techniques and Quality of Indonesian-English Translation of Captions in Pekalongan Batik Museum - Nurpermadi, Erwin Dwi; Hartono, Rudi; Sutopo, Djoko (Universitas Negeri Semarang, 2020)
This study aims to classify and identify how the translation techniques and quality achieved in Indonesian-English translation of Captions in Pekalongan Batik Museum. The aim is broken down into translation techniques, accuracy, acceptability, readability, and the translation quality influenced by translation techniques. The data of this study is the captions in Pekalongan batik museum written in Indonesian and English. The limitation of this study covers up the translation techniques and quality of Indonesian-English Translation of captions in Pekalongan Batik Museum. Descriptive qualitative research is employed in this study. The data gathered through 331 sentences for translation techniques and 30 texts in the form of captions for being investigated in translation quality. The results show that thirteen of the eighteen translation techniques proposed by Molina and Albir (2002) are chosen by the translator. They are: literal translation, reduction, borrowing, addition, generalization, modulation, established equivalent, transposition, adaptation, particularization, linguistic amplification, linguistic compression, and calque. The result of the analysis in the translation quality shows that the captions in Pekalongan batik museum as accurate, acceptable, and readable translation.